(untitled) (Journal of Face Aesthetics, 2021)
Botulinum toxin, produced by the bacteria Clostridium botulinum, paralyzes muscle contraction by inhibiting the conduction of nerve impulses. Injections of the preparation are widely used as a non-surgical method of improving the face appearance. The mentalis muscles and the surrounding soft tissue are considered key structures in lower facial rejuvenation treatments.The ability to precisely locate the muscle is a challenge for every doctor who performs treatments with the use of neurotoxin and determines therapeutic success. The muscle extends 5–10 mm from the midline and 20–30 mm from the horizontal line joining the mouth, and is present at a depth of 6.7–10.7 mm under the skin. Typically, a single midline injection of 4 to 10 units of onobotulin, incobotulin, parabotulin or 12–30 U of abobotulin is sufficient. Two injections laterally from the center of the chin are allowed, using 4–5 units of the toxin (12–15 U for abobotulin). The aim of the article is to review the use of neurotoxin injection into the mental muscle in aesthetic medicine procedures.